Understanding the Unique Effects of Identity in Adjustment Among Veterans. (2nd October 2021) - Meca, Alan; Allison, Kelsie K.; Ayers, Kenneth L.; Carr, Kyla; Cox, Sean; Bravo, Adrian J.; Davies, Rachel; Kelley, Michelle L.
Abstract: Reintegration to civilian life among service members can be understood through the lens of a transformation in an individual's identity structure. However, limited research has examined the unique impact of military, U.S., and personal identity on mental health and substance use among veterans. The goal of the present study was to examine the relationship between personal, military and U.S. identity dimensions (i.e., commitment, affirmation, and centrality) on substance use and mental health symptoms (i.e., posttraumatic stress, suicidal ideation, anxiety, and depression) in a sample of U.S. military veterans. Within our sample of military veterans ( n  = 195), a plurality were female (53.3%), White (73.3%), and veterans of the Navy (45.1%) who reported a mean age of 35.12 years (SD = 9.60). Results indicated personal identity commitment, and U.S. affirmation were associated with lower levels of substance use and symptoms of PTSD, suicidal ideation, anxiety, and depression. Military identity centrality was associated with higher levels of PTSD symptoms. Taken together, our findings provide preliminary cross-sectional support for the role that personal, military and U.S. identity play in mental health. Future longitudinal research is necessary to establish the directional relationship between identity (across various domains) and mental health and substance abuse across the transition to civilian life.